THE INFLUENCE OF TRUST, PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON INTENTION TO USE FINTECH PEER2PEER LENDING (Case Study of New User on Using Kredivo Application in West Jakarta) - Muhammad Fadhillah Mursyid (Universitas Mercu Buana, 2022)
This Study from Kredivo, Kredivo is one of the providers of digital credit card services to provide instant credit without using a card. was founded by Akshay Garg as CEO of the FinAccel company, with the aim of making choices for people who do not or do not yet have a conventional bank and expanding financial services in Indonesia. Kredivo considers millennial generation as the most potential segment. As many as 85 percent of Kredivo's credit service users are millennial. The biggest difficulty experienced by most millennials is that credit applications are rejected because the portfolios are not convincing banks. The purpose of this paper is to analyze the Influence of trust, perceived usefulness and perceived ease of use. Evidence support by collecting the data with questionnaire and take people who know Kredivo and have an intention to use it in West jakarta. as a population and the number population is unknown. The sample method that uses for this paper is purposive sampling technique and using Heir calculation to determine the number of samples and the result need 120 samples or respondent or more in order to obtain more representative data. The PLS method to analyze and describing the data. The result of the study indicates that Trust has a positive and significant effect to intention to use, perceived usefulness has a positive and significant effect to intention to use and perceived ease of use has a positive and significant effect to intention to use. Keywords: Intention to Use, Trust, Perceived Usefulness, Perceived Ease of Use, Kredivo, Online based loan.